Descriptive Analisis of Italian Students’ Preferences Regarding the Study of Spanish Language with Digital Images - Ferré Galvañ, Álvaro; María Teresa,; Martín Sánchez, María Teresa (Didáctica. Lengua y Literatura, 2025)
This quantitative study investigates the Spanish learning preferences among Italian high school students, focusing on the use of digital images with interactive tasks in reflective and creative communicative contexts. The main objective is to investigate the motivation and willingness of learners to integrate visual elements in language acquisition, as well as their usefulness for multimodal argumentation. To this end, a validated ad hoc questionnaire was used and an exploratory analysis of the collected data was carried out. The results of the exploratory analysis reveal a marked preference for the didactic effectiveness of illustrative and symbolic semiosis that complements verbal texts, and confirm the value of the recursiveness of said images in creative writing tasks and critical text comments. These conclusions open innovative expectations of discursive transmodalization in the incipient pedagogy of multimodal argumentation, suggesting the need to continue investigating the integration of visual and technological resources to optimize the learning of Spanish as a foreign language.
Keywords: digital image; Spanish Foreign Language; learning educational choice; multimodal argumentation